Manganese catalyzed reductive amination of aldehydes using hydrogen as a reductant. Issue 34 (10th April 2018) - Wei, Duo; Bruneau-Voisine, Antoine; Valyaev, Dmitry A.; Lugan, Noël; Sortais, Jean-Baptiste
Abstract : The first alkylation of amines via reductive amination of aldehydes catalyzed by a manganese bidentate pyridinyl–phosphine complex. Abstract : A one-pot two-step procedure was developed for the alkylation of amines via reductive amination of aldehydes using molecular dihydrogen as a reductant in the presence of a manganese pyridinyl-phosphine complex as a pre-catalyst. After the initial condensation step, the reduction of imines formed in situ is performed under mild conditions (50–100 °C) with 2 mol% of catalyst and 5 mol% of t BuOK under 50 bar of hydrogen. Excellent yields (>90%) were obtained for a large combination of aldehydes and amines (40 examples), including aliphatic aldehydes and amino-alcohols.